Calming the Mind, Sharpening Focus: The Role of Murattal Al-Qur'an in Students’ Concentration - Riady, Muhamad Antos; Tazkia, Nur; Rahmi, Sakinah Alvian; Susanti, Rila Renita; Lusyiawati, Okka (Universitas Islam Negeri Raden Intan Lampung, 2024)
The effectiveness of the learning process is not only determined by grades but also depends on an individual's capacity for concentration and focus. This study aimed to examine the effectiveness of listening to Qur'anic murattal recitation on concentration. The research subjects were students with average IQ levels, with each group consisting of 10 individuals. The research method used was an experimental design, specifically the randomized two-group pretest-posttest design. The experimental group listened to Qur'anic murattal recitation for 30 minutes, while the control group listened for 10 minutes. The measurement tool used was the digit span test, both backward and forward. The statistical analyses used were independent and paired sample t-tests. The results of the independent sample t-test showed a t-value of 2.105 (p ≤ 0.05), indicating a difference in the average concentration scores between the experimental group (M = 2.2; SD = 1.32) and the control group (M = 0.7; SD = 1.83). Furthermore, the results of the paired sample t-test in the experimental group showed a difference in concentration levels before listening to the Qur’anic murattal recitation (M = 9.3; SD = 2.16) and after listening (M = 11.5; SD = 1.43), with a t-value of -5.284 (p < 0.01). It can be concluded that listening to Qur’anic murattal recitation for a longer duration was effective in improving concentration. Keywords: Murattal Al-Qur'an, student’s concentration